A dual injury of the shoulder: acromioclavicular joint dislocation (type IV) coupled with ipsilateral mid-shaft clavicle fracture. (23rd November 2015) - Madi, Sandesh; Pandey, Vivek; Khanna, Vikrant; Acharya, Kiran
Abstract : A direct blow to the shoulder, as may be sustained in a road traffic accident (RTA), can result in various combinations of fracture dislocations in the shoulder joint complex. Among these, a rare variety is an acromioclavicular joint (ACJ) dislocation coupled with ipsilateral mid-shaft clavicle fracture. Diverse treatment options have been described in the literature, ranging from non-operative and operative, to hybrid management. Treatment for this complex injury is predominantly dictated by the type of dislocation and displacement of the clavicle fracture, as well as age and demand of the patient. Acute high grades of ACJ dislocation require restoration of the coracoclavicular relationship (in place of torn coracoclavicular (CC) ligament) by some form of internal fixation, thereby maintaining the ACJ reduction. An arthroscopic reinstatement of the coracoclavicular relationship using a dog bone button and fibre tape implant for this composite injury pattern has not been previously described. Furthermore, a comprehensive review of the literature associated with this injury pattern is briefly described.